Colored zirconia with high absorbance and solar selectivity. (September 2020) - Sani, Elisa; Sciti, Diletta; Capiani, Claudio; Silvestroni, Laura
Abstract: White Zirconium oxide is featured by low absorptance, but addition of specific secondary coloring agents enables to increase its solar selectivity comparable to that of conventional materials used in solar power plants. Colored zirconia, generally used for decorative purposes, has thus the possibility to widen its application fields and to be a cheaper competitor of other non-oxide materials that require expensive processing routes. Optical characterization put forth this novel aspect for constituting bulk solar absorbers operating at high temperatures. Graphical abstract: Image, graphical abstract